PENGARUH KEPRIBADIAN RASULULLAH SAW TERHADAP PERKEMBANGAN PERADABAN ISLAM - Junadi Arsyad (Tazkiya: Jurnal Pendidikan Islam, 2016)
Prophet Muhammad SAW. is the messenger of Allah. Who has issued his people from ignorance and abandon injustice and hostility to the life of knowledge and noble. He built them on the basis of civilization in accordance with the demands of the spirit and soul, so that his followers were able to lead the world for centuries when they cling to these foundations. With limited space and time, there are at least five Prophet personality that may be mentioned in this article among the many great personalities mentioned. By studying and practicing the personality of the Prophet, his companions and the message of God's fighters have managed to change the environment that originally there was no ethics filled with robbery and injustice become the people who interactive with the noble and good and became a pioneer of science and culture. So powerful was the influence that personalities makes revival of scientific and civilization in the note of history that built and run with the basics of civilization Prophet as in this paper.Keywords: Influence, Personality, Islamic Civilization